2022
DOI: 10.5902/1980509865035
|View full text |Cite
|
Sign up to set email alerts
|

Macrofauna epiedáfica em áreas submetidas a tecnologias de restauração florestal no sul do Brasil

Abstract: Objetivou-se caracterizar a composição da macrofauna epiedáfica, em áreas em processo inicial de restauração florestal, por meio de diferentes tecnologias restauradoras e comparar esses parâmetros com uma floresta-referência. O estudo foi realizado na área experimental de Restauração ecológica da UTFPR, Dois Vizinhos, Paraná, em blocos casualizados, composto por três tratamentos (RP-restauração passiva, PAD-plantio em alta diversidade e NC-nucleação) com quatro repetições. Adjacente, encontra-se o fragmento de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The advancement of technology in forest resource management is critical to attaining sustainability and enhancing efficiency. By cultivating an environment that promotes innovation and adopts state-of-the-art technologies, regions and provinces can more effectively confront the obstacles and prospects associated with forest utilization and conservation [72,73]. Studies have found that to facilitate technological advancements in the administration of forest resources, it is recommended that regions and provinces allocate resources towards research and development, capitalizing on tools including blockchain, artificial intelligence, satellite imagery, drones, and the Internet of Things.…”
Section: Malmquist Total Factor Productivity Index Resultsmentioning
confidence: 99%
“…The advancement of technology in forest resource management is critical to attaining sustainability and enhancing efficiency. By cultivating an environment that promotes innovation and adopts state-of-the-art technologies, regions and provinces can more effectively confront the obstacles and prospects associated with forest utilization and conservation [72,73]. Studies have found that to facilitate technological advancements in the administration of forest resources, it is recommended that regions and provinces allocate resources towards research and development, capitalizing on tools including blockchain, artificial intelligence, satellite imagery, drones, and the Internet of Things.…”
Section: Malmquist Total Factor Productivity Index Resultsmentioning
confidence: 99%